A dual-frequency temporal-geometric phase unwrapping based on computer-generated frequency-carrier Moiré profilometry. (15th August 2022) - Li, Hongmei; Cao, Yiping; Wu, Haitao; Xu, Cai; Zhang, Hechen; An, Haihua
Highlights: Two different gratings are skillfully designed to calculate two AC components. The AC components are used to calculate the frequency-carrier Moiré patterns. Only two deformed patterns are required to calculate the absolute phase. The constraint relationship between the two gratings will be more relaxed. The complex surface and multiple isolated objects can be reconstructed. Abstract: A dual-frequency temporal-geometric phase unwrapping based on computer-generated frequency-carrier Moiré profilometry is proposed. While two gratings with different frequencies but share the same direct current component are projected, both alternating current components of two deformed patterns can be skillfully calculated. They are multiplied by a sine function and a cosine function with the highest frequency to extract the computer-generated frequency-carrier Moiré fringe as purely as possible and to efficiently calculate the frequency-carrier wrapped phases. One artificial absolute phase is used to aid the low-frequency phase unwrapping, which assists the high-frequency phase unwrapping. It can relax the restriction of the frequency selection in traditional temporal phase unwrapping, and a higher measuring accuracy can be obtained. Meanwhile, the number of required patterns is reduced to the least two, significantly improving the measurement speed and making it suitable for real-time measurement. The experimental results verify the feasibility and flexibility of the proposed method.